2005
DOI: 10.3121/cmr.3.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin - A Novel Bone Growth Factor

Abstract: Lactoferrin is an iron-binding glycoprotein that belongs to the transferrin family. It is present in breast milk, in epithelial secretions, and in the secondary granules of neutrophils. In healthy subjects lactoferrin circulates at concentrations of 2-7 x 10 -6 g/ml. Lactoferrin is a pleiotropic factor with potent antimicrobial and immunomodulatory activities. Recently, we have shown that lactoferrin can also promote bone growth. At physiological concentrations, lactoferrin potently stimulates the proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
102
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 55 publications
2
102
1
1
Order By: Relevance
“…17,18 In primary osteoblasts, lactoferrin stimulated proliferation and differentiation and even acted as a survival factor, thereby, inhibiting apoptosis induced by serum withdrawal and also inhibiting osteoclastogenesis in a murine bone marrow culture. 19 To the best of our knowledge, effects of lactoferrin on the response to insulin (through p473Ser AKT) have never been explored. We aimed to investigate the effects of different lactoferrin concentrations on insulin-induced 473Ser AKT phosphorylation in human hepatocarcinoma (HepG2) and 3T3-L1 fibroblast mouse cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 In primary osteoblasts, lactoferrin stimulated proliferation and differentiation and even acted as a survival factor, thereby, inhibiting apoptosis induced by serum withdrawal and also inhibiting osteoclastogenesis in a murine bone marrow culture. 19 To the best of our knowledge, effects of lactoferrin on the response to insulin (through p473Ser AKT) have never been explored. We aimed to investigate the effects of different lactoferrin concentrations on insulin-induced 473Ser AKT phosphorylation in human hepatocarcinoma (HepG2) and 3T3-L1 fibroblast mouse cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The low-density lipoprotein receptor-related protein-1 and -2 (LRP1 and LRP2) are considered primary LF receptors. Although members of the LRP family are generally considered as endocytic receptors, LRP1 can also function as a signaling receptor [29]. The key to understanding the molecular basis of LF various activities is thought to reside in part according to patterns of glycosylation [37].…”
Section: Introductionmentioning
confidence: 99%
“…3) Recent studies at the cellular level have demonstrated that lactoferrin promoted the growth of bone-forming osteoblasts and inhibited their apoptosis, suggesting that lactoferrin acted as an osteogenic cytokine. 4) Lactoferrin also inhibits the osteoclastic differentiation and bone resorbing activities. Those beneficial effects of lactoferrin implicate its usefulness as a therapeutic agent in bone tissue regeneration.…”
mentioning
confidence: 99%